Beneficial Effects of Tannic Acid on the Quality of Bacterial Communities Present in High-Moisture Mulberry Leaf and Stylo Silage - Wang, Cheng; Pian, Ruiqi; Chen, Xiaoyang; Lv, Hongjian; Zhou, Wei; Zhang, Qing (Frontiers in Microbiology, 2020)
Tannic acid (TA), a type of polyphenol, is widely distributed in plants, especially in legumes. Not only does it possess antimicrobial properties, it also has the ability to bind with proteins. The fermentation parameters, nitrogen fractions, antioxidant capacity, and bacterial communities present in mulberry leaves and stylo (Stylosanthes guianensis) ensiled with or without 1% and 2% TA per kilogram of fresh matter were investigated after 75 days’ fermentation. The results showed that 1% and 2% TA both significantly decreased the butyric acid content (4.39 and 7.83 g/kg dry matter, respectively) to an undetectable level in both mulberry leaf and stylo silage. In addition, 2% TA significantly increased the contents of lactate (24.0 to 39.0, 8.50 to 32.3 g/kg dry matter), acetate (18.0 to 74.5, 9.07 to 53.3 g/kg dry matter), and the antioxidant capacity of both mulberry leaf and stylo silage, respectively. Both 1% and 2% TA also significantly decreased the pH values (5.55 to 5.04 and 4.87, respectively) and ammonia-N (85.5 to 27.5, 16.9 g/kg total nitrogen, respectively) in stylo silage. In addition, TA increased the relative abundance of Weissella, Acinetobacter, and Kosakonia spp. and decreased that of undesirable Clostridium spp. TA can thus be used to improve the silage quality of both mulberry leaf and stylo silage, with 2% TA being the better concentration of additive to use.